Purification of Mogroside V from Crude Extract of Siraitia grosvenorii Using Boronic Acid-Functionalized Silica Gel and Its Hypoglycemic Activity Determination - Yanmei Xu; Laiming Li; Pingyi Zheng; Ran Zhao; Mengqi Cheng; Yanfang Su; Jame J. Bao; Youxin Li (Separations, 2025)
Mogroside V crude extract from Siraitia grosvenorii has many pharmacological effects, such as anti-diabetes, antioxidant, etc. It is being used as a kind of natural sweetener in more and more countries. The improvement of Mogroside V purity can greatly promote the utilization value of Siraitia grosvenorii and the quality of related products. For this paper, a boronic acid-functionalized silica gel adsorbent (SiO2-GP-APBA) was synthesized and applied for the first time in the purification of mogroside V from the crude extract of Siraitia grosvenorii. It was demonstrated that it was 30–100 μm with 163.1 μmol/g of boronic acid groups on the surface of silica gel and stable at below 380.20 °C. Its maximum adsorption capacity to mogroside V was up to 206.74 mg/g at room temperature. After the saturated absorption from the crude extract of Siraitia grosvenorii in a pH 3 solution, 96.36% mogroside V could be released from SiO2-GP-APBA using a pH 7 aqueous solution, which was better than ethanol. The purity of mogroside V was significantly increased from 35.67% to 76.34%. Semi-preparative HPLC could further improve the purity of mogroside V to 99.60%. Additionally, the direct inhibition effect of the mogroside V on α-glucosidase was determined for the first time. Its inhibitory constant was 46.11 μM, indicating mogroside V was beneficial for the treatment of diabetes.